Eksplorasi Etnomatematika Tentang Aritmatika Pada Permainan Congklak - Mustofa Ali Maksum; Nufi Nuraini; Izul Zuniarsih; tika septia (CONSISTAN (Jurnal Tadris Matematika), 2025)
This research aims to study the arithmetic concept of the traditional Congklak game. In this study, researchers used ethnographic qualitative research. Data were collected through observation techniques, interviews, and documentation. Observation forms, field notes, and documentation were used to collect data. The results show that the concept of arithmetic is the four basic principles of arithmetic: addition, subtraction, multiplication, and division. By teaching the idea of arithmetic in the traditional Congklak game, social sensitivity, ability, and a sense of creativity can be fostered in students to win this game. So that teachers can design lesson plans for addition, subtraction, multiplication, and division using games method.